A Novel Site-Specific Integration System for Genetic Modification of Aspergillus flavus. Issue 2 (1st February 2020) - Tao, Fang; Zhao, Kai; Zhao, Qianqian; Xiang, Fangzhi; Han, Guomin
Abstract: Aspergillus flavus is a fungus that produces aflatoxin B1, one of the most carcinogenic secondary metabolites. Understanding the regulation mechanism of aflatoxin biosynthesis in this fungus requires precise methods for genomic integration of mutant alleles. To avoid the disadvantage of DNA integration into the genome by non-homologous or ectopic recombination, we developed a novel strategy for site-specific integration of foreign DNA by using a carboxin-resistant sdh2 R allele (His 249 Leu). Our results demonstrated that the transformants were generated with a high efficiency (>96%) of correct integration into the sdh2 -lcus of the genome of A. flavus NRRL 3357. The advantage of this method is that introduction of the eGFP expression cassette into the sdh2 -locus had little effect on fungal growth and virulence while also being rapid and efficient. This system will be a valuable tool for genetic manipulation in A. flavus . To the best of our knowledge, this is the first report on the efficient site-specific integration at the sdh2 -locus in the genome of Aspergillus .